Beispiel Nr: 37
$ \text{Gegeben:} y=ax^2+bx+c \\ \text{Gesucht:} \\ \text{Scheitel und Scheitelform}\\ \text{Definitions- und Wertebereich} \\ \text{Nullstellen - Schnittpunkt mit der x-Achse} \\ \text{Faktorisiere Form} \\ \text{Scheitel} \\ Eigenschaften\\ \textbf{Gegeben:} \\ y=-1x^2-1x+2\\ \\ \textbf{Rechnung:} \\\bullet \text{Funktion} \\ y=-1x^2-1x+2\\ \\ \bullet \text{Scheitelberechnung } \\ \begin{array}{l|l|l} \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=-1x^2-1x+2 \\ y=-1(x^2+1x-2) \\ y=-1(x^2+1x+\left(\frac{1}{2}\right)^2-\left(\frac{1}{2}\right)^2-2) \\ y=-1[(x+\frac{1}{2})^2-\left(\frac{1}{2}\right)^2-2] \\ y=-1[(x+\frac{1}{2})^2-\frac{1}{4}-2] \\ y=-1[(x+\frac{1}{2})^2-2\frac{1}{4}] \\ y=-1(x+\frac{1}{2})^2+2\frac{1}{4} \\ Scheitel(-\frac{1}{2}/2\frac{1}{4}) \end{array} & \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=-1x^2-1x+2 \\ y=-1(x^2+1x)+2 \\ y=-1(x^2+1x+\left(\frac{1}{2}\right)^2-\left(\frac{1}{2}\right)^2)+2 \\ y=-1[(x+\frac{1}{2})^2-\left(\frac{1}{2}\right)^2]+2 \\ y=-1[(x+\frac{1}{2})^2-\frac{1}{4}]+2 \\ y=-1(x+\frac{1}{2})^2+\frac{1}{4}+2 \\ y=-1(x+\frac{1}{2})^2+2\frac{1}{4} \\ Scheitel(-\frac{1}{2}/2\frac{1}{4}) \end{array} & \begin{array}{l} \text{Scheitelformel} \\ \hline y=-1x^2-1x+2 \\ xs=-\frac{-1}{2\cdot \left(-1\right)} \\ xs=-\frac{1}{2} \\ ys=2-\frac{\left(-1\right)^2}{4\cdot\left(-1\right)} \\ ys=2\frac{1}{4} \\ Scheitel(-\frac{1}{2}/2\frac{1}{4})\\ y=-1(x+\frac{1}{2})^2+2\frac{1}{4} \end{array} \\ \end{array} \\ \\ \\\bullet\text{Definitions- und Wertebereich:}\qquad \mathbb{D} = \mathbb{R} \qquad \mathbb{W} = ]-\infty;2\frac{1}{4}]\\ \\=-1(x+2)(x-1)\\ \\\bullet \text{Nullstellen / Schnittpunkt mit der x-Achse:} \\y=-1x^2-1x+2 = 0 \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ -1x^{2}-1x+2 =0 \\ x_{1/2}=\displaystyle\frac{+1 \pm\sqrt{\left(-1\right)^{2}-4\cdot \left(-1\right) \cdot 2}}{2\cdot\left(-1\right)} \\ x_{1/2}=\displaystyle \frac{+1 \pm\sqrt{9}}{-2} \\ x_{1/2}=\displaystyle \frac{1 \pm3}{-2} \\ x_{1}=\displaystyle \frac{1 +3}{-2} \qquad x_{2}=\displaystyle \frac{1 -3}{-2} \\ x_{1}=-2 \qquad x_{2}=1 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ -1x^{2}-1x+2 =0 \qquad /:-1 \\ x^{2}+1x-2 =0 \\ x_{1/2}=\displaystyle -\frac{1}{2}\pm\sqrt{\left(\frac{1}{2}\right)^2- \left(-2\right)} \\ x_{1/2}=\displaystyle -\frac{1}{2}\pm\sqrt{2\frac{1}{4}} \\ x_{1/2}=\displaystyle -\frac{1}{2}\pm1\frac{1}{2} \\ x_{1}=1 \qquad x_{2}=-2 \end{array}\\ \end{array}\\ \underline{x_1=-2; \quad1\text{-fache Nullstelle}} \\\underline{x_2=1; \quad1\text{-fache Nullstelle}} \\ \\ \bullet \text{Vorzeichentabelle:} \\ \begin{array}{|c|c|c|c|c|c|c||} \hline & x < &-2&< x <&1&< x\\ \hline f(x)&-&0&+&0&-\\ \hline \end{array}\\ \\ \underline{\quad x \in ]-2;1[\quad f(x)>0 \quad \text{oberhalb der x-Achse}}\\ \\ \underline{\quad x \in ]-\infty;-2[\quad \cup \quad]1;\infty[\quad f(x)<0 \quad \text{unterhalb der x-Achse}}$